Polityczne konteksty twórczości Tadeusza Micińskiego. Sprawa polska a Rosja w dobie Wielkiej Wojny - Sobieraj, Sławomir (Przegląd Wschodnioeuropejski, 2023)
The general purpose of the article is to show Tadeusz Miciński’s attitude to Polish – Russian relations during the First World War, with a particular emphasis on Polish independence issues. After a detailed analysis of Miciński’s literary and journalistic works from that period, the evolution of his views is identified in this range. The article shows that his favorable attitude towards Russia in the first two years of the war resulted from his belief that the tsar`s empire was able to guarantee Polish autonomy. Miciński shared the idea of a Slavic community to defeat the German enemy. He put his faith in the feasibility of Russian promises included in the statement of Grand Duke Nikolay from 1914. Moreover, Miciński relied on the Triple Entente of the UK, France and Russia, which was supposed to be the guarantor of defeating the Central Powers, and above all, Germany. Additionally, there is a description of Miciński’s attitude to post-revolutionary Russia, his hope for the democratization of the country and later disappointment that was caused by the Bolshevik coup. Miciński warned his compatriots of succumbing to ideas spread by Lenin. It has been shown that Miciński, in his views, was always a supporter of independent Poland over party divisions